2023
DOI: 10.1371/journal.pone.0280290
|View full text |Cite|
|
Sign up to set email alerts
|

Investigation of inerter-based suspension systems for heavy vehicles

Abstract: The inerter is a two-terminal component that can be added to the spring-and-damper configuration of a suspension system. It has the property that the force exerted is proportional to the relative acceleration at its terminals. Studies have demonstrated the inerter’s benefit of providing superior vibration isolation when it is used in the vehicle suspension of passenger cars. However, similar benefit on another common vehicle class on the roads, namely heavy vehicles, remain to be shown, as these vehicles have … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 23 publications
0
3
0
Order By: Relevance
“…in which 𝜌𝜌 is density of slider or flywheel, t is thickness of slider or flywheel, 𝑑𝑑 𝑖𝑖 is inner diameter of flywheel, a is distance between tangential center of flywheel and hollow slot, while e is position of slider with respect to rotational speed of flywheel. In this case, the position of sliders can be determined as Equation (7). As in structural diagram of variable inertia flywheel in Figure 1, the centrifugal force of flywheel when rotating is balanced by the spring force attached with slider in the flywheel.…”
Section: Design and Modeling Of A Variable Inertermentioning
confidence: 99%
See 1 more Smart Citation
“…in which 𝜌𝜌 is density of slider or flywheel, t is thickness of slider or flywheel, 𝑑𝑑 𝑖𝑖 is inner diameter of flywheel, a is distance between tangential center of flywheel and hollow slot, while e is position of slider with respect to rotational speed of flywheel. In this case, the position of sliders can be determined as Equation (7). As in structural diagram of variable inertia flywheel in Figure 1, the centrifugal force of flywheel when rotating is balanced by the spring force attached with slider in the flywheel.…”
Section: Design and Modeling Of A Variable Inertermentioning
confidence: 99%
“…The inerter is not only proven to be beneficial to a typical passenger car, but also on heavy vehicles such as truck and bus [6]. It is able to reduce the sprung mass acceleration and dynamic tire load of heavy vehicles with larger optimum inertance than that for passenger cars no matter in series or parallel arrangement layouts [7].…”
mentioning
confidence: 99%
“…Two types of vehicle ISD suspension layouts are designed and analyzed in the frequency domain, and it is shown that the vibration in the ofset frequency bands of the body resonance can be suppressed by vehicle ISD suspension [12]. Moreover, the performance of heavy vehicles with inerter is greatly improved; the research indicates that the vertical vibration of heavy vehicle can be efectively reduced by the vehicle ISD suspension, and it is more prominent in the low frequency band [13,14].…”
Section: Introductionmentioning
confidence: 99%